2015
DOI: 10.1097/md.0000000000002262
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Clopidogrel and Clinical Outcome When Clopidogrel Is Coadministered With Atorvastatin and Lansoprazole

Abstract: This prospective, randomized, nonblind, controlled trial evaluated the effects of clopidogrel on platelet function upon coadministration with atorvastatin and lansoprazole.One hundred four adult patients with non-ST-segment elevated acute coronary syndrome (NSTE-ACS) who underwent percutaneous coronary intervention (PCI) with drug-eluting stent implantation were included. All patients were treated with standard dual antiplatelet therapy (DAPT) plus rosuvastatin 10 mg daily after the operation. On the sixth day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 37 publications
0
29
0
5
Order By: Relevance
“…Three trials were adjudicated as having overall low risk of bias; the remaining trials were adjudicated as having an overall high risk of bias (Figure 2). Only six and eight trials were adjudicated as low risk of bias in the domains for ‘selective reporting’ and ‘allocation concealment’ respectively. More than 75% of the trials were at unclear or high risk of financial bias (‘other bias’ domain), mostly because there were no declarations about funding at all.…”
Section: Resultsmentioning
confidence: 99%
“…Three trials were adjudicated as having overall low risk of bias; the remaining trials were adjudicated as having an overall high risk of bias (Figure 2). Only six and eight trials were adjudicated as low risk of bias in the domains for ‘selective reporting’ and ‘allocation concealment’ respectively. More than 75% of the trials were at unclear or high risk of financial bias (‘other bias’ domain), mostly because there were no declarations about funding at all.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline characteristics of the patients in the 4 RCTs [ 5 , 6 , 8 , 30 ] and 8 controlled observational studies [ 7 , 9 , 13 , 25 29 ] are shown in Table 3 . The study sample sizes ranged from 104 to 8582 patients.…”
Section: Resultsmentioning
confidence: 99%
“…All 12 articles [ 5 9 , 13 , 25 30 ] reported MACE as a primary endpoint. It occurred in 1580 of the 16,839 patients (9.38%) in the PPI group, and 1281 of 16,632 patients (7.70%) in the placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…If an alternative PPI has to be considered, in vitro studies using human liver microsomes have confirmed that PPIs like rabeprazole, lansoprazole, dexlansoprazole, and pantoprazole do not show evidence of mechanism-based inhibition [29]. Clinical studies have also reported that effects of lansoprazole and pantoprazole on clopidogrel antiplatelet activity are not as potent as omeprazole [43][44][45]. When clopidogrel and PPI coadministration is necessary, switching to a PPI other than omeprazole or esomeprazole may be considered, in light of the evidence presented herein.…”
Section: The Case Of Omeprazole and Clopidogrelmentioning
confidence: 99%